Preparation for Facing the World of Work for Fresh Graduates at SMK N 9 Jakarta, Indonesia - Bintara, Rista; Fitria, Giawan Nur; Pernamasari, Rieke; Budyastuti, Triyani; Purwaningsih, Sri (MOVE: Journal of Community Service and Engagement, 2025)
Indonesia has the second-highest unemployment rate in Southeast Asia, reaching 5.45% in February 2023. Vocational High Schools (SMK) are designed to prepare graduates to be job-ready in accordance with government regulations. However, SMKs face several issues, such as misalignment between the curriculum and labor market needs, lack of mental preparedness among students, and limited collaboration with industry. The Community Service team from Universitas Mercu Buana is conducting an initiative to improve competency literacy, leadership skills, and mental readiness among students of SMK N 9 Jakarta Barat, preparing them for the workforce. This program aims to enhance competency literacy, leadership character, and mental preparedness in students to face the challenges of the job market.